„PRZYSZYWANI SYBIRACY”. KAZACHSTAŃSCY POLACY W RODZIMYM DYSKURSIE NAUKOWYM - Wiktoria KUDELA-ŚWIĄTEK (Etnografia Polska, 2014)
Researchers studying their own minorities often rely on experiences taken from their own cultures, and usually explain historical events and narrative biographies through already known lenses such as national history and culture, so that they become more familiar to the readers. In case of the Poles from Kazakhstan, a commonly used point of reference for the Polish researchers are the narratives of the so-called “Sybiraks”, deported to Kazakhstan during the Second World War. There is a visible tendency to unify the experiences of the Kazakhstani Poles and the so-called “Sybiraks”, and to present the former as the “forgotten Sybiraks”, “secular Poles” etc . The imposition of the “Sybirak rethoric” obliges the researchers to study only those biographical threads which are common for the Kazakhstani Poles and the wartime deportees from the Eastern voivodeships of the Second Polish Republic (the so-called Sybiraks). The authors are trying to avoid any difficult or controversial subjects, such as the participation of the Kazakhstani Poles in the socio-political life in the Soviet Union, political reporting, everyday life in kolkhozs, career in the Party, nationality conversions etc. After comparing the available literature of the subject with results of my own research, I conclude that the narratives of the Kazakhstani Poles are created in a completely different way than the “Sybirak” ones, with which the Polish reader is familiar through the memoir literature, radio programs and films. because they are rooted in very different sources, and the urge to talk about the past repressions is mainly aimed at drawing attention of the Poles in the fatherland towards the fact of their existence and the right to describe themselves as Poles, not at preserving the memory of their fate as the deportees.